Powered swing-by maneuvers around the Moon - Silva, A. F.; Prado, A. F.B.A.; Winter, O. C. [UNESP] (IOP Publishing, 2013)
A Swing-By maneuver occurs when a satellite approaches a celestial body to gain or lose energy from its gravitational field. The present work studies Swing-By maneuvers that are combined with the use of an impulsive thrust in different directions during the passage of the spacecraft by the periapsis of its trajectory around the Moon. The main objective of this type of maneuver is the fuel economy for orbital transfers. From the results, it is visible that the best direction to apply the impulse is not the direction to the motion of the spacecraft, as might be expected. In fact, by using a different direction, it is possible to maximize the effects of the Swing-By by decreasing the periapsis distance and/or increasing the turning angle of the maneuver, that are the key parameters to specify the variation of energy due to the Swing-By. The changes in the periapsis distance and turning angle cause modifications in the geometry of the original Swing-By, generating a maneuver with new parameters. This new Swing-By compensates for the loss of energy transfer that results of applying the impulse in a in a non-tangential direction.